PENGARUH PENGGUNAAN GAME EDUKASI WORDWALL TERHADAP MINAT BELAJAR AQIDAH AKHLAK SISWA - Nur Hikmah Okti Sania Putri; Sholihul Anshori (Kampus Akademik Publiser, 2024)
This study aims to: 1) Determine the interest in learning Aqidah Akhlaq after using the Wordwall educational game, and 2) Analyze the effect of the Wordwall educational game on the learning interest of Aqidah Akhlaq among class X students in MAN Jombang. Using a quantitative approach with a quasi-experimental posttest-only control group design, the sample consisted of 25 control and 25 experimental class students selected through purposive sampling. Data were collected via questionnaires and documentation. The results indicate that the interest in learning Aqidah Akhlaq increased, with an average value of 53.00. There is a significant influence of the Wordwall educational game on the learning interest of Aqidah Akhlaq, with a Sig value of 0.023 (< 0.05). It can be concluded that the Wordwall educational game effectively increases the learning interest of Aqidah Akhlaq among class X students from a state senior high school (Madrasah Aliyah Negeri) in Jombang.